Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/jm300507d
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Low Molecular Weight, Stable, Potent, and Long-Lasting GPR103 Aza-β3-pseudopeptide Agonist

Abstract: 26RFa, a novel RFamide neuropeptide, is the endogenous ligand of the former orphan receptor GPR103. Intracerebroventricular injection of 26RFa and its C-terminal heptapeptide, 26RFa((20-26)), stimulates food intake in rodents. To develop potent, stable ligands of GPR103 with low molecular weight, we have designed a series of aza-β(3)-containing 26RFa((20-26)) analogues for their propensity to establish intramolecular hydrogen bonds, and we have evaluated their ability to increase [Ca(2+)](i) in GPR103-transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 63 publications
0
62
0
Order By: Relevance
“…However, 9RFa has not been detected in tissue extracts to date. Structure-activity relationship studies have revealed that the synthetic C-terminal heptapeptide (26RFa 20-26 ; GGFSFRFamide) is responsible for the biological activity of 26RFa/QRFP (Le Marec et al 2011, Neveu et al 2012. A reverse pharmacological study has demonstrated that 26RFa/QRFP is a natural ligand for the previously identified orphan receptor, GPR103 (QRFPR), as described below (Fukusumi et al 2003, Jiang et al 2003, Takayasu et al 2006.…”
Section: Unity and Diversity Of The Structure Of 26rfa/qrfp In Vertebmentioning
confidence: 99%
“…However, 9RFa has not been detected in tissue extracts to date. Structure-activity relationship studies have revealed that the synthetic C-terminal heptapeptide (26RFa 20-26 ; GGFSFRFamide) is responsible for the biological activity of 26RFa/QRFP (Le Marec et al 2011, Neveu et al 2012. A reverse pharmacological study has demonstrated that 26RFa/QRFP is a natural ligand for the previously identified orphan receptor, GPR103 (QRFPR), as described below (Fukusumi et al 2003, Jiang et al 2003, Takayasu et al 2006.…”
Section: Unity and Diversity Of The Structure Of 26rfa/qrfp In Vertebmentioning
confidence: 99%
“…Recent investigations into the structure activity relationship of QRFP-26 and its analogues have led to the development of analogues which bind to the GPR103 receptor with high potency. Analogues of QRFP-26 (20–26) have been developed which bind with high potency to GPR103, are more stable than QRFP (20–26), more potent in mobilizing intracellular Ca + + and exert a long-lasting orexigenic effect in mice [64, 65]. The development of these analogues increases the potential for therapeutic applications in feeding-related disorders and future emphasis should be placed on determining the mechanisms by which the QRFP peptides and analogues alter the motivation to eat and other motivated behaviors.…”
Section: Future Of Qrfp and The Regulation Of Fat Intakementioning
confidence: 99%
“…The Fmoc‐amino acids carried the protection groups Cys‐Trt, Hyp‐t‐Bu, Trp‐Boc, Gln‐Trt, His‐Trt, Ser‐t‐Bu, Asp‐ O‐t‐Bu, Lys‐Boc, Glu‐O‐t‐Bu, Arg‐Pbf, Asn‐Trt, and Tyr‐t‐Bu. The Fmoc‐aza‐β 3 ‐amino acids were synthetized as previously described . The peptides were cleaved off the resin and deprotected for 4 h at room temperature with trifluoroacetic acid (TFA) (Fluorochem Ltd, Derbyshire, UK)/H 2 O/TIS (triisopropylsilane) (Aldrich) (95/2.5/2.5, 4 h) for peptides without Cys, with Cys the peptide was cleaved and deprotected with TFA/H2O/TIS/EDT (94/2.5/2.5/1, 4 h).…”
Section: Methodsmentioning
confidence: 99%